2021
DOI: 10.3390/children8090768
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obstructive Sleep Apnea: Knowledge and Attitudes of Medical and Dental Students and Fresh Graduates from Saudi Arabia

Abstract: This study aimed to assess the knowledge level and attitudes of graduating Saudi medical and dental students and fresh graduates from those faculties about pediatric obstructive sleep apnea (OSA), and the relation of their knowledge level to sociodemographic variables. In this cross-sectional study, 722 graduating students and fresh graduates were requested to answer a questionnaire pretested for validity and reliability. The data were analyzed statistically. Results revealed that medical participants scored 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(63 reference statements)
1
6
1
Order By: Relevance
“…In our study less than half of the participants correctly recognized the definition of OSA, which is consistent with the findings of Alosaimi et al and Xu et al's studies [ 8 , 10 ], but contrary to the results of Bashir et al's study, where a large percentage responded correctly [ 7 ]. Moreover, our findings revealed that most of our participants did not agree that OSA can impact educational performance, which is similar to the results of Alosaimi et al's study and a study conducted among medical and dental students and fresh graduates (interns) [ 8 , 11 ]. These results highlight the need for increased efforts to raise awareness about the definition of OSA and its potential impacts on children's health and academic performance.…”
Section: Discussionsupporting
confidence: 86%
“…In our study less than half of the participants correctly recognized the definition of OSA, which is consistent with the findings of Alosaimi et al and Xu et al's studies [ 8 , 10 ], but contrary to the results of Bashir et al's study, where a large percentage responded correctly [ 7 ]. Moreover, our findings revealed that most of our participants did not agree that OSA can impact educational performance, which is similar to the results of Alosaimi et al's study and a study conducted among medical and dental students and fresh graduates (interns) [ 8 , 11 ]. These results highlight the need for increased efforts to raise awareness about the definition of OSA and its potential impacts on children's health and academic performance.…”
Section: Discussionsupporting
confidence: 86%
“…The level of awareness regarding pediatric OSA among parents was only assessed in one study involving 675 parents, with nearly one-third found to have lower levels of awareness [10]. Other studies in the dental field have revealed a less-than-optimal understanding of OSA [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, insufficient attention has been paid to nighttime symptoms, such as grinding and snoring. It is interesting to note that in our study, 20% of the dentists involved claimed they did not usually attend to hypertrophic tonsils, while in the study by Alharbi et al, 96.2% of dentists and 97% of physicians correctly identified it as a risk factor for OSA in children, and likewise in other studies by Uong et al and Tamay et al, 85.9 and 95% of physicians, respectively, believed that adenotonsillar hypertrophy was the most frequent contributing factor for OSA in young patients ( 19 , 32 , 35 ). Furthermore, Alharbi et al found that only 21.4% of the dentists and 23.6% of the physicians were informed of the prevalence of OSA in children, similar to the results of this study (20%).…”
Section: Discussionmentioning
confidence: 78%
“…The results showed that only one-third of the interviewed participants had received training in pediatric OSAS during the degree course. Similarly, in a study by Alharbi et al ( 32 ), approximately half of the participants (45, 4%) were unaware if their undergraduate curriculum included information on pediatric OSA. Therefore, in this study, this apparent conflict could be partly explained by considering the age range of the sample and the recently increasing interest in sleep medicine.…”
Section: Discussionmentioning
confidence: 87%